TIME VALUE OF MONEY AND SHARIA LEGITIMACY - Mujahidin Mujahidin (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2022)
Islamic economics is an economy based on profit sharing. Money is objects approved by society as an intermediary tool for exchange exchange/trade. In a profit-sharing economy, what is used for the economic mechanism is the ratio of profit sharing and business returns that occur regularly real. This is the meaning of Islamic teachings which advocate using the concept of economics Value of Time. That is, it is time that has economic value, not money time value. The factor that determines the value of time is how a person is take advantage of that time. The more effective (appropriate) and efficient (right way), then the time value will be higher